Spherical particles formation under biaxial cyclic loading due to mesotunneling effect - A. Shanyavskiy (Fracture and Structural Integrity)
Fatigue fracture surfaces of Al-based alloys with fatigue striations pattern and such wear debris pattern as spherical particles were investigated fractographically, on the bases of the OG’e spectroscopic analysis. The sequence of events during fatigue crack edges opening was discovered when the elliptical or spherical shapes of wear debris build up on the fracture surface in crosspieces between mesotunnels under mode III of mode I fatigue crack opening because of volume rotation. The cause of black colour of places with fretting patterns on the fracture surfaces of Al-based alloys is discussed.